Plant mites of the Dominican Republic, with a description of a new species of Petrobia (Tetranychina) Wainstein, 1960 (Acari, Prostigmata, Tetranychidae) and a key to the species of this subgenus - Martínez, Leocadia Sánchez; Flechtmann, Carlos H.w.; de Moraes, Gilberto J. (Zootaxa, 2014)
Fourteen mite species of plant-associated mites of the suborder Prostigmata are reported from the Dominican Republic. Four of these refer to new findings for the country, including Petrobia (Tetranychina) hispaniola n. sp. Sánchez & Flechtmann, described from specimens collected from leaves of Citrus sp. (Rutaceae) and Rosa sp. (Rosaceae). A key for the separation of the world species of Petrobia (Tetranychina) is presented.